Kelayakan Media Pembelajaran Booklet Buah Hyphaene thebaeca (L.) Mart - Ruqiah Ganda Putri Panjaitan*; Titin Titin; Eko Sri Wahyuni (Jurnal Pendidikan Sains Indonesia, 2022)
Learning that is carried out using learning media is proven to be easier to understand and makes learning more fun. This study aims to determine the feasibility of booklets as learning media. The method used is research and development. The stages of this research include analyzing potential and problems related to learning media, collecting information on learning media booklets, designing and compiling booklets, validation by two validators, and revising products based on suggestions from validators. The assessment of the feasibility of the booklet includes aspects of format, content, and language. The validation results were then analyzed using Gregory's calculations. The results of this study indicate that the validity value of the format aspect, content aspect, and language aspect is 1.00 each, and the average validity value of the three aspects is 1.00. Overall, the criteria for the validity of the booklet are very high and the booklet is worthy of being used as a learning medium